Understanding urban networks through accessibility - Jianquan Cheng; Frank Le Clercq; Luca Bertolini (European Regional Science Association (ERSA), 2005)
The question to be investigated in the paper is how to characterize urban networks, taking both place-bound activities and (quality of) transport networks into account. The description should help formulate planning questions about the development of urban networks. Urban networks can morphologically be characterized as concentrations of land uses in a geographical area. Beyond this morphological description, places in the area can also be characterized by the amount and diversity of activities to be accessed by means of a physical transport network. So, each place can be valued in terms of opportunities within reach, depending on its links to the transport network, the attractiveness of activities within given travel time or costs, and spatial interaction with other places. The changes of activities at one place (e.g. amount of workers or jobs) can thus, in combination with changes in the transport network (e.g. travel speeds), influence the position of places elsewhere because of competition between places. The process of influence will be spatially diffused further. It indicates that spatial competition is a hidden determinant of an urban network. The paper will illustrate these different components of the urban network for the northern part of the Randstad Holland conurbation (the greater Amsterdam area) by means of different accessibility measures. The comparisons between the patterns of two urban networks (morphological and opportunity based, or 'virtual') can help explore the changing urban network, giving rise to planning questions such as: -what should be the planning aim for urban networks: making places more homogenous, more diverse or rather make them subject to (controlled) competitive developments? -improvements in the transport system may have more or less exogenous impacts on the competitive position of urban places. How should these impacts be acknowledged in transport planning? -are comprehensive planned (and controlled) interventions thinkable in urban networks, or are urban networks rather the outcome of adaptively evolving, and necessarily partial planning interventions, as those responding to traffic congestion, the need for urban expansion, changes in location preferences, etc.? Answers to these questions will be tentatively addressed to formulate a planning research agenda for urban networks.
Keywords: 330